Bats associated to caves in Jalisco, Mexico - Ayala Téllez, Héctor Leonel; Iñiguez-Davalos, Luis Ignacio; Olvera-Vargas, Miguel; Vargas-Contreras, Jorge Albino; Herrera-Lizaola, Oralia Araceli (THERYA, 2018)
Roost selection is important for bats, not only because roosts provide protection against predators but also because they provide stable environmental factors that can help them to optimize their physiological response and maintenance. For a high number of bat species, caves are an extremely important resource, sometimes housing a large number of individuals. In Jalisco, so far have been registered 72 species of bats, which equals 52 % of the bats in the country. However, little is known about which species utilize caves as habitat, including the abundance of their populations. The aims of this study were: 1) to identify some of the main cave roosts for bats in the State of Jalisco, 2) to describe the richness and composition of bat ensembles associated to caves in Jalisco, and 3) to link the distribution of bats among the caves with some environmental factors. Using previous records and references, 21 caves with presence of bats were located and surveyed. We conducted bat captures to identify these species and for those individuals for which their capture was not possible, we used ultrasonic recordings. We estimated the number of individuals using different techniques. A Non-Metric Multidimensional Scaling analysis (NMDS) was used to determine if there is a spatial pattern relationship between bat species and caves. Also, a Canonical Correspondence Analysis (CCA) was conducted to explore which environmental variables explain the spatial pattern of distribution of bats recorded in this study. In the 21 surveyed caves, we found 23 bat species, accounting for 32 % of the bat fauna in Jalisco (six species were identified using ultrasonic calls). The NMDS ordination analysis separated the species of bats in three main groups: one is associated to hot and humid caves, the second included species living in cool and dry caves, and a third group which was related to a cave of higher altitude, associated with temperate habitats. The CCA reported that temperature and humidity of the cave and the altitude as the most important variables for some groups of bats. The richness and abundance of bats were variable among caves and were associated to factors such as the intrinsic requirements of the species, physical conditions of the cave, and to the degree of human disturbance observed in each cave. The association of environmental variables and the presence and the number of bats was statistically significant, particularly with temperature and relative humidity in the case of hot caves, and with altitude for other species of bats. This work contributes to establish a baseline on the knowledge of the cave bats in the State of Jalisco. Some of the caves must be considered as priority for conservation, either for harbor a high number of individual sor a high species richness.